Business Development At Bumdes Jati Makmur Jatirejo Village, Tikung District, Lamongan Regency - Evi Fitrotun Najiah; Henny Mahmudah; Dhita Dhora Damayanti; Nabila zakiyatul Imamah (Cv. Utility Project Solution, 2022)
BUMDes is an opportunity for the village to build itself as a locomotive of prosperity for itself. Evidently, since the Village Fund was disbursed, thousands of villages have produced BUMDes with brilliant achievements, not only being able to create high rupiah profits but also being able to solve various social problems themselves. In order for BUMDes to be able to develop and build their welfare, it is necessary to specifically design BUMDes training that will provide understanding and ability for village officials and BUMDes administrators to form, manage and develop their BUMDes into BUMDes that are able to give birth to social benefits as well as profit-generating business units. BUMDes training materials combine an understanding of the philosophy of BUMDes, understanding of BUMDes with all its scope, roles and responsibilities of village governments, BUMDes and BPD administrators to how BUMDes are able to analyze the potential of their villages through special analysis techniques. Thus, it is hoped that from this training activity, BUMDes Jati Makmur, Jatirejo Village, is able to exist and always develop activities well.